Immunoblot analysis of antigens from Parastrongylus cantonensis, P. costaricensis and P. malaysiensis using serum antibodies against P. cantonensis - Eamsobhana, P.; Yong, Hoi Sen; Ambu, S. (Japanese Society of Tropical Medicine, 2000)
Parastrongylus cantonensis, P. costaricensis and P. malaysiensis adult worm antigens were tested for cross-reactivities in immunoblots using sera from patients with parasitologically confirmed parastrongyliasis. Sera from P. cantonensis-infected patients with a high specificity for the 31-kDa diagnostic P. cantonensis antigen cross-reacted with a corresponding component found in P. costaricensis and P. malaysiensis. The immune sera consistently recognized a prominent immunogenic band with a MW of 31 kDa against the antigens prepared from the 3 Parastrongylus species. Sera obtained from patients infected with Gnathostoma spinigerum and normal healthy control sera did not react with the 31-kDa protein from the 3 species of Parastrongylus. The cross-reactivity observed in the immunoblots performed on serum samples from patients with P. cantonensis infection indicates that the 3 Parastrongylus species share the specific 31-kDa antigen. This protein may be used for the immunodiagnosis of human infection with P. costaricensis and P. malaysiensis.